PENGARUH PERLAKUAN AWAL (PRE-TREATMENT) TERHADAP MUTU KERUPUK REBUNG (The Effect of Pre-Treatment on the Quality of Bamboo Shoots Crackers) - Mutiara Balqis; Ismed Suhaidi; Sentosa Ginting (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT This research was aimed to know the effect of pre-treatment to produce bamboo shoot crackers with good quality. This research was conducted using a completely randomized design (RAL) with two factors, namely the immersion media (M) : water, sodium metabisulphite, sodium chloride, and calcium carbonate and the soaking time (L) : 12 hours, 24 hours, 36 hours, and 48 ​​hours. The results showed that the effect of immersion media had a highly significant effect on ash content, score value (bamboo shoot slices and before frying), and hedonic value of after frying taste. The soaking time had a highly significant effect on water content, ash content, protein content, HCN content (bamboo shoot slices and before frying), score value of color (bamboo shoot slices and before frying), hedonic value of aroma and taste (after frying), and consumer acceptance. The interaction of immersion media and the soaking time had significant effect on the hedonic value of after frying taste. The immersion media of natrium metabisulphite and the soaking time of 48 hours had a best effect on quality of bamboo shoot crackers. Keywords: Bamboo Shoots, Crackers, Immersion Media, Soaking Time, Sodium Metabisulphite ABSTRAK Penelitian ini dilakukan untuk mengetahui pengaruh perlakuan awal untuk menghasilkan kerupuk rebung dengan mutu yang baik. Penelitian ini dilakukan menggunakan rancangan acak lengkap (RAL) dengan dua faktor, yaitu media perendaman (M) : air, natrium metabisulfit, natrium klorida, dan kalsium karbonat dan lama perendaman (L) : 12 jam, 24 jam, 36 jam, dan 48 jam. Hasil penelitian ini menunjukkan bahwa pengaruh media perendaman memberikan pengaruh berbeda sangat nyata terhadap kadar abu, nilai skor warna (irisan rebung dan sebelum penggorengan), dan nilai hedonik rasa sesudah penggorengan. Lama perendaman memberikan pengaruh berbeda sangat nyata terhadap kadar air, kadar abu, kadar protein, kadar HCN (irisan rebung dan sebelum penggorengan), nilai skor warna (irisan rebung dan sebelum penggorengan), nilai hedonik aroma dan rasa (sesudah penggorengan), dan penerimaan konsumen. Interaksi media perendaman dan lama perendaman memberikan pengaruh berbeda nyata terhadap nilai hedonik rasa sesudah penggorengan. Media perendaman natrium metabisulfit dan lama perendaman 48 jam memberikan pengaruh terbaik pada mutu kerupuk rebung.   Kata kunci : Kerupuk, Lama Perendaman, Media Perendaman, Natrium Metabisulfit, Rebung Bambu